(untitled) (Altre Modernità, 2020)
This article deals with the figure of a foreigner who finds refuge in Paris in Salim Bachi’s novel, Amours et aventures de Sindbad le Marin. The character manages to leave and follows the literary marks in this city he is discovering. The finding of the city is linked both to cultural and literary references. The streets travelled and drawn by the walker he is becoming. From this foreigner’s eyes, Paris shows hidden faces and shadow, previous and nowadays migrants. Thus who remind the character that he is himself in exile in this capitale. He is having a particular relationship by becoming a Sorbonne’s student to proof that he owns a cultural capital.